ملامح المدينة المعاصرة و مفهوم المحلة السكنية - Al Shammari, Dr. Nasser (Journal of Planner and Development, 2004)
The research target is to Know the extent influence of the neighborhood planning and architectural concept on the cities. as the importance of the residential areas represent 40-60% from the cities areas gives, The neighborhood planning concepts their important and their effects on the type of the urban physical pattern mode formation The formation of the residential areas correlated organically with physical structure and geographical environment which grow organically parallel to the city expansion and population increase. The residential neighborhood development influenced by social, economical and cultural environment of the cities according to the special and time which defined it's concept. Also the research acquainted with influence of the developments which draw main features of the physical structure of the cities throw the era because each period has it's filled with delineated contents and it's functional, diminutions, formation The research attempt on the factors which developed the concept of the neighborhoods influenced the type of the constructional formation and architectural features of the cities according to the changes in the concept. The research contrite on the organically correlated between the city and neighborhoods which participated on drawing special clear features for the city appearing it's privacy specially it's special characteristics for it's special and it's periods.